2018
DOI: 10.4186/ej.2018.22.5.227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effect of Median U-Turns on Multilane Primary Highway Capacity in Thailand through Traffic Micro-Simulation Models

Abstract: This article aims to analyze the effect of median U-turns and estimate the capacity of primary highways in Thailand using a traffic micro-simulation model. Six-lane and four-lane primary highways were selected for the study. The base condition results determined that the maximum capacity of a six-lane primary highway was 2,130 passenger cars/hour/lane, while the four-lane primary highway capacity was recorded as 2,194 passenger cars/hour/lane. Both results were slightly higher than those of the HCM2010 approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The AHP technique has been used extensively to solve practically all forms of transportation issues. Chaipanha et al (2018) conducted a study to evaluate the effect of median U-turns on multilane primary highway capacity in Thailand. Their research focused on using traffic micro-simulation models to estimate the impact of median U-turns on driving behavior and highway capacity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The AHP technique has been used extensively to solve practically all forms of transportation issues. Chaipanha et al (2018) conducted a study to evaluate the effect of median U-turns on multilane primary highway capacity in Thailand. Their research focused on using traffic micro-simulation models to estimate the impact of median U-turns on driving behavior and highway capacity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their research focused on using traffic micro-simulation models to estimate the impact of median U-turns on driving behavior and highway capacity. This study is particularly relevant as it directly addresses the evaluation of median U-turns on highway capacity, which is a key aspect of the multi-criteria decision-making process in transport engineering (Chaipanha et al, 2018). In addition, Al-Sahili et al ( 2018) investigated and modeled illegal U-turn violations at medians of limited access facilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for the effects of U-turns, Tanwanichkul et al found that vehicles executing U-turns through median U-turn openings impede vehicles in the through traffic lanes, especially when the number of turning vehicles is large. This in turn reduces the capacity of the segment [27]. Similarly, Wu et al found that U-turning vehicles obstruct traffic in the U-turning lane as well as for the adjacent through lanes.…”
Section: Introductionmentioning
confidence: 97%